Growth and Proline Content of Irradiated in Vitro Shoots of Ubi Kuning Cassava Genotype Cultured at Different Temperatures - Supatmi, Supatmi; Rahman, Nurhamidar; Hartati, N Sri (ANNALES BOGORIENSES, 2018)
Cassava (Manihot esculenta) is an important crop to food security under climate change due to its various tolerance mechanism under stress conditions. However, the sustainable growth of cassava in the field depends on many factors especially temperature. The objective of the research was to investigate the growth performances and proline contents of irradiated Ubi Kuning at dosage of 10 Gy, cultured in Murashige Skoog (MS) hormone-free solid medium for 4 weeks at three different temperature treatments i.e 25oC, 28oC and 30oC. Each treatment consisted of 3 clone explants with 5 replicates. Results show that growth performances of irradiated plantlets were better compared to that of non-irradiated plantlets in terms of plant height and number of leaves at all temperature tested. The best growth performances were obtained from irradiated plantlets grown under 30oC. The proline content of irradiated Ubi Kuning was high when they were grown under 25 oC and 30oC, implying that these plantlets had the possibility to tolerant to lower and higher-temperature condition. This study is initially useful to find out the growth ability of irradiated Ubi Kuning in response to lower and higher temperature.